Land - use intensification trends in the Rio de la Plata region of South America : towar specialization or recoupling crop and livestock production - Faccio Carvalho, Paulo César de (2021)
Fil: Faccio Carvalho, Paulo César de. Federal University of Rio Grande do Sul. Integrated Crop-Livestock Systems Research Group. Porto Alegre, Brazil.